The Atlantic connection: coastal habitat favoured long distance dispersal and colonization of Azores and Madeira by Dysdera spiders (Araneae: Dysderidae). Issue 8 (17th November 2021) - Crespo, Luís C.; Silva, Isamberto; Enguídanos, Alba; Cardoso, Pedro; Arnedo, Miquel A.
Abstract : The woodlouse hunter Dysdera spiders have colonized all Macaronesian archipelagos. We report here for the first time an evolutionary connection between the Iberian Peninsula, Madeira, and the remote archipelago of Azores. Based on museum specimens from the 1950s, we describe the first endemic Dysdera species from the Azores. Additionally, we report the recent collection of immature individuals related yet probably not conspecific to the new species, rejecting previous suggestions that the endemic lineage had gone extinct. A multi-locus target phylogeny revealed that an undescribed species from Madeira was the closest relative to the Azores lineage, and that both island taxa were in turn sister to an Iberian endemic species, within a mostly Iberian clade. Interestingly, the Madeiran relative was not closely related to the remaining endemic species reported in the archipelago, suggesting an independent colonization. A divergence time estimation analysis unravelled that Dysdera colonized both archipelagos early after their emergence. The colonization pathway remains ambiguous, but the Iberian Peninsula acted as the ultimate source of the ancestral colonizers. Finally, we describe the new species Dysdera cetophonorum Crespo & Arnedo sp. nov. from Pico and Dysdera citauca Crespo & Arnedo, sp. nov. from Ilhéu de Cima (Porto Santo) and redescribe and illustrate the female genitalia for the first time of their poorly known closest relative, Dysdera flavitarsis Simon, 1882 from the north-western Iberian Peninsula. http://zoobank.org/urn:lsid:zoobank.org:pub:1E75CCEC-1632-4581-93A5-E61721970022